Primary Small Cell Carcinoma of the Larynx: Report of a Rare Tumor - Harmeet Singh; Ashok Chauhan (Case Reports in Oncological Medicine)
Primary small cell carcinoma of larynx is a rare tumor representing less than 0.5% of all laryngeal cancers. This is one of the most lethal of all malignancies associated with frequent early widespread metastases and dismal prognosis. We report a case of a 60-year-old patient with small cell carcinoma of the subglottic larynx, who presented with hepatic metastasis.